2018
DOI: 10.4149/neo_2018_170906n575
|View full text |Cite
|
Sign up to set email alerts
|

Identification of critical microRNAs in gastrointestinal stromal tumor patients treated with Imatinib

Abstract: Gastrointestinal stromal tumors (GISTs) are the most common mesenchymal neoplasms of the gastrointestinal tract. Imatinib mesylate was considered to be a breakthrough drug in clinical treatment of GIST, but GIST patients showed resistance against it. We aimed to identify critical microRNAs (miRNAs) related to imatinib resistance in imatinib-treated GIST patients. Microarray datasets under the accession number of GSE63159 and GSE45901 were downloaded from the Gene Expression Omnibus (GEO) database. The differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Also, the integrin-mediated signaling transduction pathway of focal adhesion kinase (FAK) was identified by the Gene Expression Omnibus (GEO) database and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis as the pathway where the significantly different ncRNAs between the imatinib treated GIST patients with and without resistance were enrich in ( Zhang et al, 2018 ). Moreover, FAK is verified as the downstream pathway of PTPN18 contributing to the imatinib resistance in GISTs, which is regulated by miRNA-125a-5p ( Akcakaya et al, 2014 ; Huang et al, 2018 ).…”
Section: Regulating Roles Of Noncoding Rna In Drug Resistance Of Gast...mentioning
confidence: 99%
“…Also, the integrin-mediated signaling transduction pathway of focal adhesion kinase (FAK) was identified by the Gene Expression Omnibus (GEO) database and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis as the pathway where the significantly different ncRNAs between the imatinib treated GIST patients with and without resistance were enrich in ( Zhang et al, 2018 ). Moreover, FAK is verified as the downstream pathway of PTPN18 contributing to the imatinib resistance in GISTs, which is regulated by miRNA-125a-5p ( Akcakaya et al, 2014 ; Huang et al, 2018 ).…”
Section: Regulating Roles Of Noncoding Rna In Drug Resistance Of Gast...mentioning
confidence: 99%
“…Being overexpressed in imatinib-resistant GIST samples and displaying a significant correlation to imatinib response, miR-28-5p has been proven to function as an oncomiR. However, very little is known about this miRNA and therefore further research is required to confirm these findings [87].…”
Section: Imatinibmentioning
confidence: 99%
“…Zhang et al performed in silico analyses using GO function and KEGG pathway enrichment as well as the lncRNA-miRNA-target gene regulatory network built of the microarray datasets deposited by Akçakaya et al [110]. These studies highlighted miR-28-5p and-not surprisingly-miR-125a-5p, both of which displayed a significant correlation to imatinib resistance and imatinib sensitivity [117]. Additionally, Shi et al uncovered a series of up-or downregulated miRNAs by comparing imatinib-naïve with imatinib-resistant GIST samples [118].…”
Section: Mirnas Related To Imatinib Resistancementioning
confidence: 99%
“…These prognostic biomarkers may be further developed into a more quantitative risk evaluation for GIST which is now based on the mitotic index, tumor size and tumor location. Finally, miRNAs associated with imatinib resistance [30,110,114,115,[117][118][119] may be used to signal evolving imatinib resistance enabling early clinical intervention. Interestingly, lncRNAs have also been identified that could be used for diagnostic purposes [129,131,133] or are specifically linked to high-risk/advanced GIST [108,122,123,125,128] and imatinib resistance [126,127,130].…”
Section: Biomarkersmentioning
confidence: 99%